Numerical study of the effects of the separation-element configuration on the characteristics of a shock tube. (December 2021) - Hernández Castro, Javier; Svete, Andrej; Kutin, Jože
Abstract: Shock tubes are used for dynamic calibrations of pressure meters in the frequency domain because they have the ability to generate a nearly ideal pressure step. If the shock tube includes a fast-opening valve, the shock wave formed in such a shock tube differs from those generated in shock tubes with a diaphragm. The paper presents a numerical study of the effects of valve geometry on shock-wave formation and flow characteristics after the shock-wave front.